Sadd al-Dzari'ah's Strategy in Maintaining Social Integrity and Sharia of Muslim Minorities amid Religious Plurality in North Sulawesi - Nasruddin Yusuf; Ridwan Jamal; Nik Abdul Rahim Nik Abdul Ghani (Qiyam Islamic Studies Center Foundation, 2025)
The Muslim minority in North Sulawesi (Indonesia) has its challenges in maintaining Islamic Sharia values amid the dominance of the majority's culture and religious practices. The incompatibility between Sharia values and social reality can cause a shift in the material truth of Islamic teachings. Promiscuity, a culture of liquor consumption, free non-halal food and drinks, and the prevalence of interfaith marriages are clear evidence of the heavy influence of the majority environment on minority Muslims. This study aims to explore how the concept of sadd al-dzari'ah is used by Muslim minorities in North Sulawesi as an alternative approach in maintaining religious identity. This study uses a qualitative approach with field study methods through interviews and observations of religious leaders, educators, and Muslim communities in minority areas. The analysis is carried out with the perspective of sadd al-dzari'ah as a preventive principle in Islamic legal methodology that aims to close the doors of harm. The findings of the study show that there are protection efforts (sadd al-dzari'ah) that are naturally built from the Muslim minority, in the form of awareness of forming communities so that religious rules and traditions become freely practiced, creating protection for halal consumption models, and strengthening family orientation and religious education. This protective effort (sadd dzariah) has proven to be more effective in maintaining the values of minority Muslim communities than relying entirely on the principle of maslahah, which is very compromising. Efforts to protect through sadd dzariah have been able to maintain the maqashid sharia concretely, especially in the maintenance of religion (hifzh al-din) and heredity (hifzh al-nasl), as well as maintaining harmony between religious communities (hifdz al-nafs). This research can recommend a disparity model to strengthen the role of religious leaders and Islamic educators in implementing Sharia preventive strategies that are adaptive to the context of a pluralistic society.